xCT: A Critical Molecule That Links Cancer Metabolism to Redox Signaling - Liu, Jinyun (Mol Ther, 2020)
System x(c)(−) cystine/glutamate antiporter, composed of a light-chain subunit (xCT, SLC7A11) and a heavy-chain subunit (CD98hc, SLC3A2), is mainly responsible for the cellular uptake of cystine in exchange for intracellular glutamate. In recent years, the xCT molecule has been found to play an important role in tumor growth, progression, metastasis, and multidrug resistance in various types of cancer. Interestingly, xCT also exhibits an essential function in regulating tumor-associated ferroptosis. Despite significant progress in targeting the system x(c)(−) transporter in cancer treatment, the underlying mechanisms still remain elusive. It is also unclear why solid tumors are more sensitive to xCT inhibitors such as sulfasalazine, as compared to hematological malignancies. This review mainly focuses on the role of xCT cystine/glutamate transporter in regard to tumor growth, chemoresistance, tumor-selective ferroptosis, and the mechanisms regulating xCT gene expression. The potential therapeutic implications of targeting the system x(c)(−) and its combination with chemotherapeutic agents or immunotherapy to suppress tumor growth and overcome drug resistance are also discussed.